Large‐scale forest composition influences northern goshawk nesting in Wisconsin1. Issue 3 (4th January 2013) - Donner, Deahn M.; Anderson, Dean; Eklund, Daniel; St. Pierre, Matthew
Abstract The northern goshawk (Accipiter gentilis atricapillus) is a woodland raptor that uses a variety of forest types for nesting across its breeding range, but strongly depends on older forests with large trees and open understories. Goshawks may select nesting locations by maximizing the convergence of nesting and foraging habitats. Insights into goshawk responses to heterogeneous landscapes can be gained by examining the location of active nest sites through time and at multiple spatial scales. We examined the landscape‐scale forest conditions that influenced the probability of active goshawk nests in the United States Forest Service, Chequamegon‐Nicolet National Forest (CNNF) in northern Wisconsin. We used goshawk nest survey and monitoring data from 1997 to 2006 to determine the probability of an active nest site over time in relation to forest composition and road density at 3 scales (200‐m, 500‐m, and 1, 000‐m radii). Goshawk nests were located primarily in upland hardwood (64%), conifer (23%), and older aspen–birch (≥26 yrs old; 11%) habitat cover types. We used Bayesian temporal autoregressive models of nest locations across multiple spatial scales to analyze these data. The probability of active goshawk nest occurrence increased with increasing conifer cover (1, 000 m) and decreased with increasing cover of older aspen–birch and density of primary roads (500 m). In addition, lesser proportions of older aspen–birch at intermediate scales around goshawk nests had a stronger effect on the probability of a nest being active than conifer and primary roads. Thus, the ratio of conifer cover (within 1, 000 m) to older aspen–birch cover (within 500 m) in landscapes surrounding nest sites was the key driver in predicting the probability of an active nest site. This finding can be used by forest managers to help sustain the active status of a goshawk nesting area through time (i.e., annually), and foster goshawk nesting activity in areas where active nesting is not currently occurring. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.